State disinformation: emotions at the service of the cause (Communication & Society, 2022)
Disinformation is not only a phenomenon of modern democratic societies, but also a tool at the service of states. In the current communication ecosystem, politics and society interrelate in the face of a phenomenon characterised by multiple information channels and sources in which emotions now play a central role. In international relations, the expression of a state’s political will through charisma and populism are the chief aspects detected in the analysis of emotions in political science. This has led to the construction of a narrative based on security threats and the friend-enemy distinction, among other things. On the basis of an exhaustive literature review, this study offers an overview of the political and social factors underlying the use of emotions in disinformation as regards four aspects: politics, economy, diplomacy and security. Likewise, it identifies the main defining traits and behaviours of domestic and international audiences. The analysis and verification of the research question contribute to elaborate an international theory of emotionally driven disinformation which has begun to play a leading role in both academia and politics.